Prevalence of Temporomandibular Joint Problems in Candidate Patients for Impacted Third Molar Surgery With and Without the Previous Temporomandibular Disorder: A Prospective Study - Hasan Mirmohamadsadeghi; Orkideh Alavi; Mohamadjavad Karamshahi; Reza Tabrizi (Wolters Kluwer Medknow Publications, 2019)
Introduction: Minor surgeries in the mouth region have been associated with a risk of temporomandibular disorders (TMDs). One of the most common surgeries is third molar removal. The aim of this study was to determine the prevalence of temporomandibular joint (TMJ) problems in candidate patients for impacted third molar surgery with and without previous temporomandibular problems. Materials and Methods: In this prospective cohort study, 15 to 30-year-old patients with and without TMD were chosen before third molar surgery. According to the clinical examinations and Research Diagnostic Criteria for TMD questionnaire, frequency of joint click, severity of TMJ pain using visual analog scale (VAS), and maximum mouth opening (MMO) were evaluated at before the surgery and 1 week, 1 month, and 6 months after the surgery. The changes in the click frequency at different times in the two groups were analyzed statistically by Chi-square test and the difference of the parameters of the MMO and VAS values in the two groups were analyzed by Student t test. Results: In the group with TMD, the click had a significant increase 1 week after the surgery. However, 6 months after the surgery, the incidence of click decreased significantly compared to 1 month after the surgery (P = 0.032). MMO at all the times was significantly higher in the group without TMD symptoms (P = 0.012). At all the times, VAS values were higher in the group with TMD symptoms (P = 0.024). The maximum VAS values were observed at 1 week after the surgery (P = 0.041). Conclusion: The reduction in MMO and increase in VAS score in patients with TMD were evident compared to patients without TMD. Furthermore, it seems that the surgical trauma resulting from the removal of the third molars is a predisposing factor for developing TMD.